CLOSTRIDIUM DIFFICILE ASSOCIATED DIARRHEA IN MULTIDISCIPLINARY HOSPITAL - N. F. Mulyar; S. A. Vereschagina; T. V. Fadeeva; G. P. Spasov; O. V. Kanya (Acta Biomedica Scientifica, 2012)
Currently, Clostridium difficile is the main reason of a nosocomial diarrhea, caused by uncontrolled antibacterial treatment. This problem is not paid, enough attention in our country. We analyzed. 536 cases of antibiotic associated infections using new immunochromotographical assay for express detection of Clostridium difficile. Since 2008 to 2011 evaluated rate of the positive tests was 28,7 % among the hospital patients. The first line therapy of this infection is vancomycine and metronidazole. We also observed increased incidence of mycosis, which accompanying the antibiotic associated diarrheas. During the same period the rate of Candida spp. infection was 50,8 % among the same patients. We used fluconazole and. amphotericine for the mycosis treatment. We also recommended to manage disbiosis during one year after discontinue of the treatment, and. we supposed reasonable to be managed by infectionist for this group of patients.